Students’ ability in writing annotated bibliography: Teaching critical writing - Retno Wulan Dari; Suvi Akhiriyah; Eva Rahmawati; Him'mawan Adi Nugroho; Twin Dyah Martiana (Universitas Merdeka Malang, 2022)
Annotated bibliographies are used in various situations. Annotated bibliography is a short-annotated list of sources that summarizes, evaluates, and states source relevance. The ability to write annotated bibliography shows one’s ability to find the right information for writing research article. This paper aims to see how the ability of second year students majoring in English is in making annotated bibliography. This research is qualitative research using data obtained from 42 students who assigned on writing annotated bibliography. Data were explained descriptively from the score mean and percentage using Turnitin then scaled them using 4-scale Linkert Scale. Results showed that of five variables, quality of sources, annotations content, overall quality were good, while accuracy and annotations structure variables were adequate. For Turnitin check, 69.05% showed good and very good quality, while only 9.52% them showed poor quality. Finally, it isindicated that most of the second-year subjects consider as having good standard abilities categorized in writing annotated bibliography. DOI: 10.26905/enjourme.v7i2.8966